2019
DOI: 10.1080/20008198.2019.1654783
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in cardiorespiratory fitness are not significantly associated with post-traumatic stress disorder symptom reduction in intensive treatment

Abstract: Background: Physical activity has been found to have positive effects on symptoms of posttraumatic stress disorder (PTSD). However, the importance and role of cardiorespiratory fitness (CRF) in relation to PTSD treatment outcome is not yet clear. Objective: The purpose of the present study was to test the hypothesis that CRF would increase following intensive trauma-focused treatment (TFT) of PTSD augmented with physical activity, and that improved CRF would be associated with a significant decline in PTSD sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…Another study showed no difference in HR or HRV for individuals engaged in mindfulness meditation or paced breathing compared to those in an active control condition (Wahbeh et al., 2016). The authors of another study found that a combination of prolonged exposure therapy, EMDR, and exercise reduced tonic BP (Voorendonk et al., 2019). A study of EMDR found improved tonic HRV but not tonic HR in a single‐arm treatment study (Sack et al., 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Another study showed no difference in HR or HRV for individuals engaged in mindfulness meditation or paced breathing compared to those in an active control condition (Wahbeh et al., 2016). The authors of another study found that a combination of prolonged exposure therapy, EMDR, and exercise reduced tonic BP (Voorendonk et al., 2019). A study of EMDR found improved tonic HRV but not tonic HR in a single‐arm treatment study (Sack et al., 2007).…”
Section: Resultsmentioning
confidence: 99%
“…The intensive trauma-focused treatment format consisted of two consecutive weeks, with 4 days of treatment each week, in which patients went home for the weekend in between (De Jongh et al, 2020 ; Van Toorenburg et al, 2020 ; Van Woudenberg et al, 2018 ; Voorendonk, Sanches, De Jongh, & Van Minnen, 2019 ; Wagenmans, Van Minnen, Sleijpen, & De Jongh, 2018 ; Zoet, Wagenmans, Van Minnen, & De Jongh, 2018 ). The intensive treatment programme is developed to treat patients suffering from severe PTSD and is specifically designed to reduce the drop-out rates for PTSD patients.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, we used traumatic films in a laboratory setting and relied on a mentally and physically healthy sample of participants. This is also reflected in our sample mean CRF (PWC 170 = 170.1, SD = 38.1), which is relatively high in comparison to other healthy samples (Bland et al, 2012), and compared to PTSD patients (Voorendonk, Sanches, De Jongh, & Van Minnen, 2019). This implies that our findings may not generalise to traumatised samples and individuals with impaired physical health, warranting complementary and more naturalistic studies, e. g., among patients with PTSD in clinical settings.…”
Section: Discussionmentioning
confidence: 62%